Sheltering and quarantine measures for risks that threaten the village of Umm al-Nasr, Gaza Strip - Musalam, PhD, Alaa M. A.; El-Ashgar, MD, Nizam M.; Al-Agha, MD, Muhammad; Abunamous, MA, Raed E. S.; Abuhabib, PhD, A. A. (Journal of Emergency Management, 2020)
This study aimed to analyze the risks that affect the Umm al-Nasr village (north of Gaza Strip), which include wars, floods, and the Corona virus disease-19 (COVID-19) pandemic, which may require the emergency committee to identify places for sanitary isolation in the case of infection or provide shelters in the disasters such as wars and floods. A plan that contains procedures for managing the displacement of the citizens according to the type of the disaster and the suggested safe shelters were prepared. Individuals infected with COVID-19 are isolated in central places or their home. Responding procedures for the emergency committee in Umm al-Nasr municipality were prepared to deal with displaced people. A mathematical model was designed to simulate choosing a shelter for the citizens of this village depending on the type of crisis. The results showed the different conditions that may affect the displacement operation, such as the type of shelter, the allocated area, the number of displaced citizens, the type of disaster, and the required speed to reach the shelter. This study recommended advancing the capabilities of the community to confront risks and COVID- 19. Besides, perfect planning plays a significant role in saving lives, time, and effort. Therefore, it is needed to cooperate with the local authorities, such as municipalities, ministry of health, civil defense, and international institutions to implement a response action during disasters, and the necessity of closing residential areas and isolating them if new cases of COVID-19 appear.